Raden Ayu Dewi Nawangsih’s Feminist Values in Kudus’ Oral Tradition Through Ethnomythology Study - Rahmania, Sofi Aulia; Widianto, Eko (Jurnal Sosiologi Agama, 2024)
The view of feminism is always related to the position and existence of women in various sectors that demand equality with men’s position. Feminism seeks to break down the patriarchal culture which is deeply rooted in Indonesia. This view even existed long before Raden Ayu Dewi Nawangsih was born as the daughter of a Sunan. This study aims to analyse the values of feminism in the oral tradition of Raden Ayu Dewi Nawangsih, which developed in the Kudus community. The methodological approach used is descriptive qualitative, using literature and field studies. At the same time, the theoretical approach used is the Levis-Strauss structural analysis. The research data is in the form of myths that contain feminist values. The method used in this research is the proficient method, literature study, and documentation. At the same time, the data analysis method consists of four stages: data transcription, data reduction (using Levi-Strauss structural theory), data interpretation, and conclusions. Based on the results of the analysis, two types of feminist values were found in the character Raden Ayu Dewi Nawangsih: personal power and freedom to choose a partner. This significant finding can be used to interpret feminism values via ethno-mythology perspective combining with structuralism approach. This interdisciplinary study would be essential to see the feminism values from oral tradition which is commonly categorized as a literary product.